Factors in the Capacity Development of Single-Industry Towns in the Republic of Kazakhstan - ABIKAYEVA, Marina; OMARKOZHAYEVA, Assem; RAKHIMOVA, Gulmira; NAZYROVA, Gulfia; KABDULSHARIPOVA, Alia (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
This paper studies the scientific basis of the origin and formation of single-industry towns, provides the definition of this concept and the methodological management framework for their development. It also analyses foreign and Kazakhstani experience of socio-economic development of single-industry towns, classifies cities with regard to the functional specialization, placement principles and other factors, identifies the criteria for designating small towns as single-industry towns and reveals common problems of their development. The authors determine the main directions of solving the problems and prove the necessity of the strategy for developing single-industry towns in Kazakhstan. The object of the research is single-industry town of the energy complex of the Republic of Kazakhstan. The paper used such general scientific methods as analysis, comparison and generalization. Due to the fact that today the problem of the development of single-industry towns experiencing economic difficulties or becoming completely uncompetitive in the new market environment is a major challenge for Kazakhstan, it is of particular attention. The economic development of the territory, the efficiency of the economy, defence capabilities, science advancement and foreign policy are the main factors for the viability of the republic, and the situation in single-industry towns determine the potential of viability of the country as a whole. The relevance and novelty of the research is as follows: the analysis of methodological approaches to the assessment of the development of single-industry towns was carried out; the main problems of the development of single-industry towns in Kazakhstan were identified; the main factors affecting the development of single-industry towns were determined.